LEGITIMASI INTERVENSI ICC TERHADAP TINDAKAN KEJAHATAN YANG DILAKUKAN MILITER AMERIKA SERIKAT DI AFGHANISTAN - Syauki Lukman Sofwan (2022)
The International Criminal Court (ICC) is the international Judicial Institution established under the Rome Statute of 1998. The ICC's jurisdiction covers the crimes of genocide, crimes against humanity, war crimes, and crimes of aggression. This study discusses the legitimacy of the ICC in cracking down on alleged crimes of the United States of America in Afghanistan, although the United States of America is not a member state of the Rome Statute of 1998. The research uses a normative juridical research method using the statute approach and case approach. The result showed the ICC has the legitimacy to take action over alleged violations committed by the United States of America Army in Afghanistan all through the United State of America is not a member state of the Rome Statute 1998throught a series of efforts of the initiative of the prosecutor of the ICC, the crime that occurred in the region of Afghanistan that has become part of the Rome Statute of 1998 and the Principles of Security Council Referral so that the intervention of the ICC can be is ustified. The conclusions of the study are based on things theoretically and juridically interrelated. The basic theoretical namely that the jurisdiction of the ICC is the implementation of the Geneva conventions of 1949 and the international community's efforts to fight the perpetrators of the crime is the most serious as well as the implementation of security council referral contained in article 13 Rome Statute 1998 and the applicability of universal jurisdiction. While the basis of the juridical is emphasized based on alleged violations of humanitarian law that is geneva conventions of 1949 and protocol enhancements which one attempts to claim the all convention also became the competence of the ICC as prosecute the parties responsible for the war crimes and genocide. Key Word: ICC; Afghanistan; United States f America; Roem Statute of 1998